The institutional origin of an international coalition in favor of the right to sport - Canan, Felipe; Rojo, Jeferson Roberto; Starepravo, Fernando Augusto (Journal of Physical Education (Maringá), 2020)
We aimed do analyze the configuration of the relationships established among intergovernmental/transnational organizations that have been ahead for institutionalizing the idea of the right to sport from 1968 to 1978. We used analysis of documents under the theoretical perspective of the Advocacy Coalition Framework. It was seen that the organizations started a coalition to defend a belief system regarding the idea of the right to sport. However, such a movement was not contrary to the elite sport. It can be concluded that the institutional construction process of the idea of the right to sport in an international context occurred in a nonconflicting way with a partnership of actions, despite a certain difference of beliefs.